Psychometric properties of the Vietnamese SDM-Q-9 for measuring patient-perceived shared decision-making in primary care - Ho, Dac Truong An; Nguyen, Minh Tam; Nguyen, Vu Quoc Bao; Vi, Thanh Dat; Ngo, Phu Hai; Nguyen, Le Tan Thien; Ngu, Van Quan; Nguyen, Thi Thu Thao; Le, Ho Thi Quynh Anh (Tạp chí Y Dược Huế, 2026)
Background: Shared decision-making (SDM) is a core component of patient-centred chronic disease care, yet little is known about how to measure patient-perceived SDM in Vietnamese primary care. This study evaluated the psychometric properties of the Vietnamese version of the 9-item Shared Decision-Making Questionnaire (SDM‑Q‑9) among adults with chronic diseases. Methods: A cross-sectional survey was conducted among patients receiving ongoing care for chronic conditions at the Family Medicine Centre, Hue University of Medicine and Pharmacy, in 2025. The SDM‑Q‑9 was translated and culturally adapted using forward-backwards translation and cognitive debriefing. Internal consistency was assessed using Cronbach’s alpha and corrected item-total correlations. Structural validity was examined using confirmatory factor analysis (CFA). Construct validity was evaluated through known-group analyses based on clinical characteristics and patient-reported experiences of consultation. Results: The Vietnamese SDM‑Q‑9 showed good internal consistency (Cronbach’s alpha = 0.81); corrected item–total correlations ranged from 0.30 to 0.68, and removing any item did not improve alpha. Early-stage SDM items showed lower factor loadings (0.32) and floor effects, whereas later-stage items demonstrated higher loadings (≥0.63) and ceiling effects. The CFA showed a poor fit for the original one-factor model (χ²/df = 10.67, RMSEA = 0.22, CFI = 0.63), and alternative models showed partial improvement (with the highest CFI of 0.73), but did not meet the conventional criteria. SDM-Q-9 scores differed by consultation-related experiences (all p < 0.01) but not by disease duration, disease control, or medication adherence (all p > 0.05). Conclusions: The Vietnamese SDM‑Q‑9 demonstrates acceptable reliability and construct validity for assessing patient-perceived SDM in chronic disease management in primary care. The findings support retaining all nine items to preserve conceptual completeness and international comparability. Further validation in larger and more diverse samples is warranted to strengthen evidence for its broader application in research, education, and quality improvement.